MWCNT based monolith for the analysis of antibiotics and pesticides in milk and honey by integrated nano-liquid chromatography-high resolution orbitrap mass spectrometry. Issue 1 (29th November 2018) - Aydoğan, Cemil; El Rassi, Ziad
Abstract : A monolith based on MWCNTs incorporated into HPMACl was prepared for use as a stationary phase in nano-liquid chromatography. Abstract : A monolith based on MWCNTs incorporated into HPMACl was prepared for use as a stationary phase in nano-liquid chromatography. The performance of the monolith was tested at 800 nL min −1, in the separation of several compounds of environmental and pharmaceutical interest, namely antibiotics and pesticides. Good resolution was observed on the MWCNT incorporated column. Excellent separation performance was obtained in most cases. The high chromatographic separation capability and great stability observed in nano LC-UV encouraged the analyses to be carried out via HR Orbitrap MS. The antibiotics and pesticides were then injected into an integrated nano LC-HR Orbitrap MS system and they were identified by their retention time and accurate mass which were measured with product ions in full MS-all-ion fragmentation mode. High sensitivity (at the ppb level) and reproducibility were obtained. The applicability of the method with the monolith was demonstrated using milk and honey samples with the LODs ranging from 0.1 to 20 μg kg −1 .